Rapamycin-induced autophagy protects proximal tubular renal cells against proteinuric damage through the transcriptional activation of the nerve growth factor receptor NGFR. Issue 6 (3rd June 2018) - Vizza, D.; Perri, A.; Toteda, G.; Lupinacci, S.; Perrotta, I.; Lofaro, D.; Leone, F.; Gigliotti, P.; La Russa, A.; Bonofiglio, R.
ABSTRACT: Experimental evidence demonstrated that macroautophagy/autophagy exerts a crucial role in maintain renal cellular homeostasis and represents a protective mechanism against renal injuries. Interestingly, it has been demonstrated that in the human proximal tubular renal cell line, HK-2, the MTOR inhibitor rapamycin enhanced autophagy and mitigated the apoptosis damage induced by urinary protein overload. However, the underlying molecular mechanism has not yet been elucidated. In our study we demonstrated, for the first time, that in HK-2 cells, the exposure to low doses of rapamycin transactivated the NGFR promoter, leading to autophagic activation. Indeed, we observed that in HK-2 cells silenced for the NGFR gene, the rapamycin-induced autophagic process was prevented, as the upregulation of the proautophagic markers, BECN1, as well as LC3-II, and the autophagic vacuoles evaluated by transmission electron microscopy, were not found. Concomitantly, using a series of deletion constructs of the NGFR promoter we found that the EGR1 transcription factor was responsible for the rapamycin-mediated transactivation of the NGFR promoter. Finally, our results provided evidence that the cotreatment with rapamycin plus albumin further enhanced autophagy via NGFR activation, reducing the proapoptotic events promoted by albumin alone. This effect was prevented in HK-2 cells silenced for the NGFR gene or pretreated with the MTOR activator, MHY1485. Taken together, our results describe a novel molecular mechanism by which rapamycin-induced autophagy, mitigates the tubular renal damage caused by proteinuria, suggesting that the use of low doses of rapamycin could represent a new therapeutic strategy to counteract the tubule-interstitial injury observed in patients affected by proteinuric nephropathies, avoiding the side effects of high doses of rapamycin.